2021
DOI: 10.1007/s11239-021-02470-y
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies in critically ill COVID-19 patients with thromboembolism: cause of disease or epiphenomenon?

Abstract: Coronavirus 2019 disease (COVID-19) is associated with coagulation dysfunction that predisposes patients to an increased risk for both arterial (ATE) and venous thromboembolism (VTE) and consequent poor prognosis; in particular, the incidence of ATE and VTE in critically ill COVID-19 patients can reach 5% and 31%, respectively. The mechanism of thrombosis in COVID-19 patients is complex and still not completely clear. Recent literature suggests a link between the presence of antiphospholipid antibodies (aPLs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 89 publications
(60 reference statements)
1
12
2
Order By: Relevance
“…Some studies found PPP >4 to be well in populations of Italy 17 and China 18 . Surprisingly, this study's results indicated that the post‐ICU admission mortality rate was 17%, which is relatively lower than initial reports among patients from China, Europe and the United States 27 . This study has some limitations.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Some studies found PPP >4 to be well in populations of Italy 17 and China 18 . Surprisingly, this study's results indicated that the post‐ICU admission mortality rate was 17%, which is relatively lower than initial reports among patients from China, Europe and the United States 27 . This study has some limitations.…”
Section: Discussioncontrasting
confidence: 79%
“…This finding is consistent with an earlier meta‐analysis showing that VTE incidence was 31% among critically ill Covid‐19 patients, followed by DVT, PE and arterial thromboembolism, 28%, 19% and 5%, respectively 26 . That study also concluded that critically ill Covid‐19 patients are at risk of thrombosis (both arterial and venous), despite heparin treatment, especially because it has been reported that older age is a potential risk factor for a more severe disease course, including in Saudi Arabia 27 . Another recent meta‐analysis found that the incidence of VTE among hospitalized Covid‐19 patients was high and was associated with an increased risk of mortality in these patients, particularly among patients in ICU 12 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Only 4% of our large cohort were diagnosed with systemic lupus erythematosus; and 2% had a diagnosis of infective endocarditis This finding is in line with previous studies that found positive anti-phospholipid antibodies to be widespread among hospitalized patients with infectious diseases, malignancies, and other conditions. 1 , 2 , 23 Our findings of the increased mortality rates amongst the low complement group remained valid regardless of the inclusion or exclusion of the SLE and infective endocarditis patients.…”
Section: Discussionsupporting
confidence: 53%
“…This may support the previous suggestion that anti-phospholipid antibodies not in the context of clinical APS may often not represent a true cause of venous hypercoagulability. [20][21][22][23] Our cohort lacked data to examine if arterial thrombosis events were the source for the increased mortality in the low complement group. The groups had similar rates of solid malignancies therefore the increased mortality was not attributed to the malignancies.…”
Section: Discussionmentioning
confidence: 99%